Poison frogs as a model system for studying the neurobiology of parental care. (December 2015) - Roland, Alexandre B; O'Connell, Lauren A
Highlights: Poison frogs are ideal for studying proximate and ultimate mechanisms of behavior. Poison frogs are a suitable animal model for field and laboratory studies. Diversity in mating behavior and parental care strategies allow comparative work. Poison frogs can address the four levels of analysis proposed by Tinbergen. Abstract : Parental care is essential for the survival and well-being of offspring in many species. Understanding the mechanisms underlying parental involvement can lend insight into general and conserved principles governing the neural basis of a major life history stage, parenthood. While many animal models of parental behavior display maternal care, studying male involvement is challenging. Male parents are usually involved in a strong relationship with their partner, and this makes separating reproductive and parental mechanisms difficult. This separation is possible in poison frogs, where different species provide biparental care and male or female uniparental care without pair bonding. Poison frogs provide a great comparative framework to study parental care within a relatively simple neural architecture easily amenable in the field and laboratory.